'I need to be there': British South Asian men's experiences of care and caring. Issue 3 (26th May 2020) - Gill, Santokh Singh
ABSTRACT: This article provides an insight into British South Asian men's experiences of care and caring. Care is gendered, however the ways in which care features in the lives of British Asian men is under-researched and demands attention, particularly given the changing demographics in the UK. The discussion draws on qualitative empirical research with a sample of British Asian men in their early thirties to early fifties. In depth interviews were conducted to consider roles and responsibilities within families and communities in relation to care, either as parents and/or as having ageing parents or grandparents. The findings give voice to British Asian men's experiences of care and enhance our understanding of care in the everyday and the complex and contested nature of contemporary British Asian masculinities. The findings challenge populist assumptions surrounding Asian men and provide an alternative insight into their experiences to highlight the centrality of care and caring in British Asian men's lives and to document that British Asian men do care. Whilst the stories of care are diverse, there is a strong sense that British Asian men value care, and place importance on being able to provide care and support to family.